1994
DOI: 10.1002/art.1780370708
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and synovial fluid hyaluronan levels

Abstract: Objective. To assess the effect of intraarticular (IA) corticosteroid on hyaluronan (HA) concentrations in synovial fluid (SF) and serum and the clearance of '311-labeled albumin from the joints of patients with rheumatoid arthritis (RA), osteoarthritis (OA), and ankylosing spondylitis (AS).Methods. SF and serum were collected before and 2 weeks and 2 months after IA steroid injection. The HA concentration was assessed using an enzyme-linked immunosorbent assay and '3'I-albumin clearance from joints was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…Indeed, soon after its isolation [Z] and chemical analysis [3], it was found that synovial fluid of normal joints contains high-Mr HA at particularly high concentrations [4]. Recent studies show that HA levels are decreased in rheumatoid joints, and that they are partly restored by intra-articular corticosteroid treatment, which concomitantly improves joint function [5,6]. This is consistent with the notion Abbreviations used: AER, apical ectodermalridge; ECM, extracellular matrix; ERM, ezrin, radixin and moesin; GAG, glycosaminoglycan; HA, hyaluronan; HABP, HA-binding protein; HAS-AP, HA-synthaseassociated protein; MAPWERK, mitogenn-activated protein kinase/extracellular-signal-related kinase; NO, nitric oxide; RHAMM, receptor for HA-mediated motility; UDPGD, UDP-glucose dehydrogenase.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, soon after its isolation [Z] and chemical analysis [3], it was found that synovial fluid of normal joints contains high-Mr HA at particularly high concentrations [4]. Recent studies show that HA levels are decreased in rheumatoid joints, and that they are partly restored by intra-articular corticosteroid treatment, which concomitantly improves joint function [5,6]. This is consistent with the notion Abbreviations used: AER, apical ectodermalridge; ECM, extracellular matrix; ERM, ezrin, radixin and moesin; GAG, glycosaminoglycan; HA, hyaluronan; HABP, HA-binding protein; HAS-AP, HA-synthaseassociated protein; MAPWERK, mitogenn-activated protein kinase/extracellular-signal-related kinase; NO, nitric oxide; RHAMM, receptor for HA-mediated motility; UDPGD, UDP-glucose dehydrogenase.…”
Section: Introductionmentioning
confidence: 99%
“…( 16 , 24 , 25 ) Extracellular matrix degradation and turnover result in the release of HA and HA fragments into the systemic circulation. ( 26 ) Different from patients who underwent anti-inflammatory treatment, low levels of HA were found in the circulation. ( 23 , 26 )…”
Section: Discussionmentioning
confidence: 99%
“…( 26 ) Different from patients who underwent anti-inflammatory treatment, low levels of HA were found in the circulation. ( 23 , 26 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve of the 29 synovial fluid proteins with significant difference between groups are commonly found in plasma, and 10 of these were decreased in the high glucosinolate group. In the inflamed joint, changes in the permeability of the synovium have been described, whereby increases in protein and solute concentration within the joint cavity have been observed 31, 32 . Resolution of aberrant synovial permeability by the high glucosinolate diet may offer one possible explanation for a reduction in the number of plasma proteins observed in this group, though this remains to be confirmed.…”
Section: Discussionmentioning
confidence: 99%